(untitled) (Journal of Health, Population and Nutrition, 2011)
Unprotected sexual intercourse among HIV-positive people can adversely affect their own health by increasing their exposure to multiple strains of HIV-1 or other sexually transmitted infections (STIs). The study explored the relationship between knowledge of Nepalese HIV-positive men about the consequences of having unprotected sex with seroconcordant partners and their intention to practise safer sex with such partners. In total, 166 participants recruited conveniently in the Kathmandu Valley, Nepal, were interviewed. Each participant reported intention to practise safer sex with seroconcordant partners, knowledge about the consequences of having unprotected sex with seroconcordant partners, perceived partnerrelated barriers to condom-use, belief that condoms interfere with sex, and condom-use self-efficacy. Of the 166 participants, 50.6% intended to practise safer sex every time they have sex with seroconcordant partners. Results of multiple logistic regression analysis showed that the participants who were aware of the possibility of HIV superinfection [adjusted odds ratio (AOR)=2.93, 95% confidence interval (CI) 1.16- 7.34, p=0.022)] or that the presence of STIs in HIV-positive persons increases progression of HIV disease (AOR=2.80, 95% CI 1.08-7.26, p=0.033) were more likely to intend to practise safer sex with seroconcordant partners. Similarly, the participants who were employed or who had lower levels of belief that condoms interfere with sex were more likely to intend to practise safer sex. The findings suggest that improving the knowledge of HIV-positive persons about the consequences of having unprotected sex with seroconcordant partners might improve their intention to practise safer sex with such partners. Key words: HIV infections; Intention; Knowledge; Knowledge, attitudes, practices; Perceptions; Safe sex; Sexual behaviour; Nepal DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7866 J HEALTH POPUL NUTR 2011 Jun;29(3):191-199